A comprehensive review of green policy, anaerobic digestion of animal manure and chicken litter feedstock potential – Global and Irish perspective. (February 2022) - Bhatnagar, N.; Ryan, D.; Murphy, R.; Enright, A.M.
Abstract: Renewable energy has become increasingly popular in the recent times as countries have shifted focus towards carbon-neutral and environmentally sustainable sources of energy. Biogas and biomethane derived energy from Anaerobic Digestion of organic waste have proved to be excellent alternative to fossil-fuel based energy. Many countries around the world are actively adopting biomethane as an alternative to petrol/diesel or use biogas to provide energy for the domestic sector through combined heat and power plants. The contribution of anaerobic digestion in the Irish energy sector remains quite low as compared to its European union counterparts due to related legislation and lack of government incentives. Nevertheless, Ireland is rich in biomass with a huge potential for developing its renewable energy sector from anaerobic digestion of agricultural waste, which is relatively inexpensive and available here in abundance. Chicken litter is one such waste which offers a variety of environmental benefits as anaerobic digestion feedstock. In comparison to cow manure and pig manure, chicken litter was relatively unpopular in anaerobic digestion due to its high nitrogen and lignocellulose content. Further, the global production of chicken manure has been increasing constantly thus making its disposal challenging across the world. However, researchers have identified many optimisation strategies to overcome these issues and demonstrated the advantages of using chicken litter in anaerobic digestion including odor reduction, greenhouse gas mitigation, production of gaseous biofuel, avoiding eutrophication of water bodies and significantly improving global production of renewable energy to help countries reduce their carbon emissions. Highlights: Advantages of AD include odor reduction, sustainable fuel production and pathogen removal. Global poultry industry is growing by 5% annually and requires sustainable disposal options like AD. Greenhouse gas mitigation by implementation of AD is important in both Irish and global scenario. Chicken litter is inexpensive waste and potential AD feedstock abundantly present in Ireland.